Prolonged administration of low-dose cytarabine and thioguanine in elderly patients with acute myeloid leukaemia (AML) achieves high complete remission rates and prolonged survival. Issue 4 (20th March 2020) - Arthur, Christopher; Jeffrey, Anthony; Yip, Eva; Katsioulas, Vicki; Nalpantidis, Anastasios; Kerridge, Ian; Greenwood, Matthew; Coyle, Luke; Mackinlay, Naomi; Fay, Keith; Enjeti, Anoop; Shortt, Jake; et al.
Abstract: The prognosis of AML in elderly patients is poor and research into novel therapeutic approaches is urgently needed. This study examined the use of low-dose chemotherapy with cytarabine and thioguanine administered in repetitive cycles in 62 elderly patients with newly diagnosed or relapsed/refractory AML. The overall response rate was 58% in the total cohort. Response rates (CR/CRi) were significantly higher in patients with newly diagnosed AML (74%) compared to patients with relapsed/refractory disease (25%, p = .0004). Kaplan–Meier estimate of overall survival was 289 days (95% CI; 183–395 days) with a relapse rate of 65.7%. The induction mortality rate was 16.1% with treatment successfully undertaken in the outpatient setting. Similar clinical outcomes were observed in a retrospective analysis of a second cohort of 25 AML patients treated at a different site. These results support the use of a sustained low intensity chemotherapy approach as a therapeutic option for elderly patients with AML.